2019
DOI: 10.1096/fj.201900887rr
|View full text |Cite
|
Sign up to set email alerts
|

Octyl itaconate inhibits osteoclastogenesis by suppressing Hrd1 and activating Nrf2 signaling

Abstract: The endogenous metabolite itaconate has emerged as a regulator of macrophage function that limits inflammation. However, its effect on cell differentiation and osteoclast‐related diseases is unclear. Here, for the first time, we explored the effect of itaconate and its cell‐permeable itaconate derivative, 4‐octyl itaconate (OI) on osteoclast differentiation in vitro and in vivo. Firstly, we demonstrated that itaconate concentration was lower in estrogen‐deficient mice. OI released itaconate and induced the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 32 publications
4
43
0
Order By: Relevance
“…In the ALI + OI group, mice were administered OI (50 mg/kg or 100 mg/kg) for three days. 16 On the third day, 2 h after the treatment with OI or DMSO, the mice were administered LPS (5 mg/kg) intratracheally. After 12 h, the mice were sacrificed, and the lung samples and bronchoalveolar lavage fluid (BALF) were harvested as described in a previous study.…”
Section: Methodsmentioning
confidence: 99%
“…In the ALI + OI group, mice were administered OI (50 mg/kg or 100 mg/kg) for three days. 16 On the third day, 2 h after the treatment with OI or DMSO, the mice were administered LPS (5 mg/kg) intratracheally. After 12 h, the mice were sacrificed, and the lung samples and bronchoalveolar lavage fluid (BALF) were harvested as described in a previous study.…”
Section: Methodsmentioning
confidence: 99%
“… 22 Nrf2 genetic or pathological deficiencies correlate with increased susceptibility to OP in mice due to an insufficient antioxidative stress capacity, 23 , 24 while enhancing Nrf2 by various activators or agonists is protective against OP. 25 , 26 The Nrf2 promoter is characterized by CpG islands, and Nrf2 downregulation due to altered DNA methylation is observed in several aging-related pathological conditions, such as aging, cancer and neurodegenerative disease, 27 , 28 suggesting that epigenetic Nrf2 suppression might contribute to the initiation or progression of OP.…”
Section: Introductionmentioning
confidence: 99%
“…ELISA results demonstrated that Sch had an anti‐oxidant effect when stimulated by RANKL (Figure 5F). Nrf2 functions as a transcriptional factor which regulates the expression of several anti‐oxidant and phase II detoxifying enzymes, hence decrease the production of ROS 9,11,12 . We then tested whether this compound could enhance the expression of Nrf2, the lynchpin factor in anti‐oxidant system, during osteoclast differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…The mRNA expression levels were assessed by real‐time PCR system (Applied Biosystems). The specific primers we used are according to a previously report unless otherwise noted 11,12,18,19 . The primers are listed in Table .…”
Section: Methodsmentioning
confidence: 99%